Раскопки городища Артезиан в Восточном Крыму в 2009 г. - Винокуров, Н.И. (Археологічні дослідження в Україні, 2010)
During the research of Artesian hill-fort the layers were uncovered on the territory of 800 m2. Cultural layers and remains of buildings of three chronological horizons related to the existence of the hill-fort during the Ancient period were found: of the edge of the millennia, from the 1st to the 2nd centuries, and from the 3rd to the beginning of the 4th centuries.